Vitiligo: A Review of Aetiology, Pathogenesis, Treatment, and Psychosocial Impact - Khadeejeh AL-smadi; Mohammad Imran; Vania R. Leite-Silva; Yousuf Mohammed (Cosmetics, 2023)
Vitiligo is an acquired, chronic condition characterised by depigmentation of the epidermis or by destruction/loss of melanin. Skin cells (melanocytes) are responsible for producing melanin, the substance that gives pigmentation to the skin. This review aims to provide a comprehensive overview of the current state of knowledge about vitiligo. Although there is no specific ethnic group, gender, or skin type that is more prone to vitiligo than others, it can affect anyone. The most commonly prescribed treatments for vitiligo are systemic and topical phototherapy and immunomodulators such as corticosteroids, calcineurin inhibitors, and vitamin D analogues, in addition to cosmetics that can camouflage and improve the quality of life. Even though vitiligo is typically thought of as a cosmetic disorder, its effects on the physical and psychosocial health of sufferers cannot be ignored.